PERTUMBUHAN MTsN 7 PADANG : STUDI SEJARAH LEMBAGA PENDIDIKAN TAHUN 1989 – 2017 - Handayani, Meri (RC-INSTITUT, 2019)
Abstrak MTsN 7 Padang is one of the formal education institutions located Jln. Kayu Aro, the village of Bungus Barat, Bungus Bay, Kabung, Padang. At first this Madrasa was named MTsN Bungus Teluk Kabung. This Madrasah was established in 1989 with the status of a private madrasah. In 1995 the madrasah changed its status to a public madrasah based on the decree of the religious department of the province of West Sumatra no. 515 A on November 25, 1995 with accreditation B, and since then the madrasah changed its name to MTsN Bungus Teluk Kabung. Continue to make improvements both in terms of physical and academic. The biggest changes experienced by this madrasah occurred in 2015, this year status of madrasah accreditation changed to A and the madrasah continued to grow until 2016. The madrasah became a madrasah a madrasah with the highest UN score in the city of Padang.in 2017 the madrasah changed its name to MTsN 7 Padang. This madrasah continues to increase from the initial only an ordinary madrasah located on the edge of the city of Padang is now on of the pre-eminent madrasah in the city of Padang that rival other madrasah in the city center. This madrasah is the main choice for people in Bungus Teluk Kabung sub-district as place of education for their children. This study aims to see the growth experienced by Padang 7 MTsN starting from the begining of its establishment until 2017. This research is a type of qualitative research with historical methods consisting of four stages namely heuristic, source criticism, interpretation and historiography.